Kegiatan Pengembangan Minat dan Bakat pada Anak - Anak dalam Kegiatan Keagamaan di Desa Lalang Kec. Tanjung Pura Kab. Langkat - Mahidin, Mahidin; Aulia, Mia; Hrp, Muhammad Royhan; Angi, Nur Fadila; Nurbaini, Nurbaini; Nuraida, Nuraida (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Every child has different potential, interests and talents. Special gifted children whose potential is optimized and properly stimulated can become one of the quality human resources owned by the country, compared to children who do not get proper stimulation. Stimulation is a variety of stimuli, such as play opportunities, learning facilities, or materials (eg stories or reading), that can trigger a child to learn or process teaching. Optimal is the highest condition in which it is possible for someone or something to do without destroying the elements that are in place. Potential are specific things that exist in children, which appear more when compared to children of their age. Interest is a strong urge for someone to do everything he wants. Whereas talent is a basic trait, intelligence and innate nature that is innate. Talent itself can be interpreted as a person's basic ability to learn in a relatively short time compared to other people, but the results are even better. In short, this is a potential possessed by a person as innate. The aim of the research is to optimize the potential, interests and talents of the children in Lalalang Village for the advancement of potential human resources in the future, namely to find out and make solutions so that the children of Lalalang Village get a direction and a place to shape their character so that they are able to understand what potential they have and are very important for the future. This research contains the reasons and the process of optimizing the potential, interests and talents of the children in Lalang Village. Keywords: Optimization, Potential, Interest, Talent, Children